2020
DOI: 10.1021/acs.jpclett.0c00464
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Thermal Conductivity in Mesoporous Silica Films Using Pore Size and Nanoscale Architecture

Abstract: This work investigates the effect of wall thickness on the thermal conductivity of mesoporous silica materials made from different precursors. Sol–gel- and nanoparticle-based mesoporous silica films were synthesized by evaporation-induced self-assembly using either tetraethyl orthosilicate or premade silica nanoparticles. Since wall thickness and pore size are correlated, a variety of polymer templates were used to achieve pore sizes ranging from 3–23 nm for sol–gel-based materials and 10–70 nm for nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…The data show that adding either 10 or 20 mol % titania resulted in reduced thermal conductivity compared to the pure silica films, presumably because all Ti incorporation provides additional centers that scattered propagons and diffusons, thus reducing the thermal conductivity of those samples, regardless of the compositional homogeneity. In agreement with this idea, PWSM fits to pure silica samples, published previously, produce a value of x = 0.31, which is higher than any of the titania-containing samples . This suggests that all titania incorporation frustrates parallel heat conduction.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The data show that adding either 10 or 20 mol % titania resulted in reduced thermal conductivity compared to the pure silica films, presumably because all Ti incorporation provides additional centers that scattered propagons and diffusons, thus reducing the thermal conductivity of those samples, regardless of the compositional homogeneity. In agreement with this idea, PWSM fits to pure silica samples, published previously, produce a value of x = 0.31, which is higher than any of the titania-containing samples . This suggests that all titania incorporation frustrates parallel heat conduction.…”
Section: Resultssupporting
confidence: 80%
“…In agreement with this idea, PWSM fits to pure silica samples, published previously, produce a value of x = 0.31, which is higher than any of the titania-containing samples. 26 This suggests that all titania incorporation frustrates parallel heat conduction. When we further compare all the samples that show titania clustering, that is, the ST10reg sample and all ST20 samples, we observe that the ST20 samples had lower thermal conductivities than the ST10reg samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the thermal conductivity of porous silica could be lower than 0.098 W mK À1 . 44 The 808 nm near-infrared laser was a thermal light source, and it produced heat in the irradiation process. The low thermal conductivity of DBs was conducive to reducing heat loss through self-insulation, which made the temperature of DBs also increase under laser irradiation.…”
Section: Photothermal Performance Of Cu-dbsmentioning
confidence: 99%
“…The kinetic theory relates the thermal conductivity of bulk silica κ SiO 2 to the phonon mean free path λ such that κ SiO 2 = 1 3 ρ SiO 2 c v , SiO 2 ν λ . Here, ρ SiO 2 is the density of silica (=2210 kg m –3 ), c v ,SiO 2 is our previously measured specific heat capacity at constant volume (=750 J kg –1 K –1 ), , and v is the average sound velocity in the material, obtained from the longitudinal v l and transversal v t wave vectors given by v = 1 3 v normall + 2 3 v normalt , with v l = 5968 m s –1 and v t = 3764 m s –1 . From this kinetic model, a phonon mean free path of λ = 0.56 nm in bulk silica (κ SiO 2 = 1.4 W m –1 K –1 ) was retrieved, which agrees reasonably well with the value of λ = 0.42 nm that was obtained from eq .…”
Section: Resultsmentioning
confidence: 99%